1997
DOI: 10.3354/meps146231
|View full text |Cite
|
Sign up to set email alerts
|

Grazing by protists and seasonal changes in the size structure of protozooplankton and phytoplankton in a temperate nearshore environment (western Gulf of St. Lawrence, Canada)

Abstract: -Grazing by protists and seasonal changes in the size structure of protozooplankton and phytoplankton in a temperate nearshore environment (western Gulf of St. Lawrence, Canada)'~e p a r t e m e n t des Sciences biologiques, Universite du Quebec i Montreal, CP 8888, MontrBal, QuBbec, Canada H3C 3P8 2~e p a r t e m e n t de Biologie, Universite Laval, QuBbec. PO, Canada G l K 7P4ABSTRACT: Seasonal changes in the biomass and size structure of phytoplankton and protozooplankton and the grazing effect of protozoop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 22 publications
5
21
0
2
Order By: Relevance
“…Aquat Microb Ecol 34: [165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180]2004 Our results show that microprotozoans can remove a significant percentage of PP (26 to 45% d -1 ), and have a much higher impact than small zooplankton (1 to 6% d -1 ). Our estimates of microprotozoan impacts are within the range found in coastal waters off Washington, USA (17 to 52%: Landry & Hassett 1982), the Baltic Sea (23%: Uitto et al 1997); and Gulf of St Lawrence (40 to 100%: Tamigneaux et al 1997). Therefore, the microheterotrophic pathway may also be an important link in highly productive upwelling areas.…”
Section: Planktonic Production and Carbon Flowsupporting
confidence: 52%
See 1 more Smart Citation
“…Aquat Microb Ecol 34: [165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180]2004 Our results show that microprotozoans can remove a significant percentage of PP (26 to 45% d -1 ), and have a much higher impact than small zooplankton (1 to 6% d -1 ). Our estimates of microprotozoan impacts are within the range found in coastal waters off Washington, USA (17 to 52%: Landry & Hassett 1982), the Baltic Sea (23%: Uitto et al 1997); and Gulf of St Lawrence (40 to 100%: Tamigneaux et al 1997). Therefore, the microheterotrophic pathway may also be an important link in highly productive upwelling areas.…”
Section: Planktonic Production and Carbon Flowsupporting
confidence: 52%
“…Carbon fixed by primary producers is transferred along upwelling food webs through both 'microbial' and 'classical' pathways, and the proportion directed along each route probably depends largely on the size of the primary producers (Walker & Peterson 1991, Mann 1992. There is increasing evidence that the microbial food web is a fundamental and almost permanent feature of not only oligotrophic but also eutrophic marine systems (Neuer & Cowles 1994, Tamigneaux et al 1997. The significance of bacteria and microprotozoans as components of the biomass, and their role in biogeochemical cycles in upwelling systems have been widely recognized (Newel & Turley 1987, Painting et al 1992, Ducklow et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that at this time, small ciliates around 15 to 30 µm in size contributed significantly to grazing loss rates on the < 5 µm size class. This result is consistent with previous studies , Tamigneaux et al 1997) that report both HNF and ciliates as significant grazers of small eukaryotes. The results overall suggest that HNF and, to a lesser extent small ciliates, play an important role by repackaging the smaller phytoplankton biomass into a size that is more accessible for larger predators and, hence, form an important link in the food web.…”
Section: Grazing On Autotrophic Components Of the Food Websupporting
confidence: 83%
“…Anderson & Fenchel (1985) and McManus & Fuhman (1986) reported HNF as the primary consumers of bacteria, while and Tamigneaux et al (1997) report ciliates < 20 µm as the dominant grazers of prey < 5 µm. suggested that elevated levels of bacterial production may selectively stimulate the growth of small (bacterivorous) ciliates.…”
Section: Importance Of Phytoplankton (Autotrophs) Versus Heterotrophsmentioning
confidence: 99%
“…Intensive feeding of copepods on protozoa is found in different marine ecosystems (Tamigneaux et al 1997, Mayzaud et al 2002, Calbet & Saiz 2005 although the intensity of this feeding process differs between systems. For example, the grazing of copepods on protozoa was only half of the grazing of copepods on phytoplankton in all seasons and for different regions in the Greenland Sea (Moller et al 2006).…”
Section: Feeding On Microbial Carbon By Copepodsmentioning
confidence: 99%